Kejawen, Multiculturalism, and Principles of the Qur’an: Transformation and Resupposition of QS. al-Kafirun (109): 6 in Urip Sejati Community of Yogyakarta - Nazifatul Ummy Al Amin; Egi Tanadi Taufik; Siti Mufidatunrofiah; Idris Ahmad Rifai (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
This article focuses on the idea of multiculturalism in Javanese mythical believing (Kejawen) communities within the paradigm of Qur'anic studies. The discussion of the research emphasizes the axiological shift of QS. Al-Kafirun (109) in the milieu of Urip Sejati community of Yogyakarta, Indonesia. “Urip Sejati” is a Javanese religious society that has developed as a minority group because it is domiciled near to various centers of Islamic civilization as pesantren, historic mosques, and colleges in Krapyak. This research has been held since 2018 by doing literary studies, observations, and interviews through the leaders of Urip Sejati community.The structure of this article features a complex process of analysis on transmission and transformation of Qur'anic interpretations in the paradigm of sociology. It also analyzes the patterns of the phenomenon in a synchronic and diachronic paradigm to get through a worldview reading. On its formal form, the reception of Q.109: 6 in the membership of Urip Sejati contains informative and performative suppositions. This verse became a major foundation for the construction of multiculturalism because it contains the doctrine acknowledged as a verse that supports pluralities.